Fair and equitable treatment of investors: a comparative appraisal - Qazi Zada, Sebghatullah; Ansari, Abdul Haseeb (Serials Publications (P) LTD, 2017)
The fair and equitable treatment of the foreign investors has become a major concern of the international community not only in developing and least developed countries – perhaps because of the absence of proper laws and their poor enforcement in these countries - but purportedly also in developed countries. Legal protection to foreign owned properties against any confiscation and treatment that is not ‘fair and equitable’ has always been a matter of great concern in international law. Host states’ standards of their treatment, specifically with respect to protecting foreign investments as well as an amicable dispute settlement mechanism are the central issues that are associated with the globalization of economy and have often led to disputes regarding access to markets, market liberalization; and consequently, the establishment and protection of rights of foreign investors. From an international law point of view, countries have the wide-rangingfreedom to regulate the entry of international investments as well as the liberty to deal with those investments. Similar provisions are also there in the Shari‘ah. It is for this reason that it is necessary to examine law and practice in some Islamic countries in order to examine as to ascertain as to how Islamic law deals with the foreign investors. Since its inception, Islam has been emphatic on the establishment of a just and equitable government based on justice (adl) and providing fair and equitable treatment to all regardless of their faith, race, or place of origin. This paper endeavors on both a conceptual analysis of the ‘fair and equitable treatment’(FET) under international investment law and Islamic law. The paper finds that there is a considerable link between the civil law on ‘fair and equitable treatment’ (FET)and its Shari‘ah perspective. Islam emphasises on fair treatment of everyone based on the principles of objectives of the Shari‘ah (maqasid al- Shari‘ah), justice (adl), equity (istihsan) and prohibition of discrimination regardless of faith, race and colour (prohibition of tafreeq). In Libyan American Oil Company(LIAMCO) v The Government of the Libyan Arab Republic [17 ILM 3 (1978)] the Ad Hoc Tribunal created under the Draft Convention on Arbitral Procedure, ILC, 1958, attempted to establish a link between ‘General Principles of Law’ and ‘Islamic Law’ pertaining to indemnification on the acquisition of the assets of the foreign company and concession rights. The paper sheds some more light on all the aspects of such a proposition in order to make it easy to resolve similar disputes involving investors in countries operating under or with Islamic countries and acceptability of such dispute resolutions.